NSTP 1 - Punzalan, Michelle D.; Tan, Nerissa P.; Maranan, Mario H. (Manila : Mindshapers Co. , Inc., 2020)
"This textbook was designed to give the students an in-depth understanding of the essence of the National Service Training Program (NSTP) as a civic education and defense preparedness program of the government of the Philippines."
Includes references.
English.
Keywords: Service training--Philippines